SISTEM FULL DAY SCHOOL SMK PEMBANGUNAN KALIANDA TAHUN PELAJARAN 2021/2022 - Rohman Efendi; Erjati abas; Etika Pujianti (UNISAN JURNAL, 2022)
This research uses qualitative research with case study design. Data and documents were collected and compiled using in-depth interview techniques, participant observation and documentation studies. The data and documents were checked for validity through triangulation of methods, theories and sources. Furthermore, the data and documents were analyzed descriptively qualitatively. The purpose of this research is to find out how the full day school system of the Kalianda Development Vocational School is. These aspects include the management of Educator Recruitment Planning, Organizing the Placement of educators and educational staff,. The most important subjects in this study were the head of the madrasa, the teachers, the school committee. The results of the analysis are stated in the main tasks and functions, the results of the analysis of this position are carried out by filling and placing personnel in positions according to intellectual capacity, capability, work experience and example. (1) the withdrawal and selection of GTT and PTT candidates is carried out based on considerations of academic achievement, non-academic, and good character. (2) the training and development of human resources that is carried out still tends to measure the success and failure of the training in terms of implementation, not oriented to whether the training is being implemented effectively. Keywords: full day school system